Particulate matter induces prothrombotic microparticle shedding by human mononuclear and endothelial cells. (April 2016) - Neri, Tommaso; Pergoli, Laura; Petrini, Silvia; Gravendonk, Lotte; Balia, Cristina; Scalise, Valentina; Amoruso, Angela; Pedrinelli, Roberto; Paggiaro, Pierluigi; Bollati, Valentina; Celi, Alessandro
Abstract: Particulate airborne pollution is associated with increased cardiopulmonary morbidity. Microparticles are extracellular vesicles shed by cells upon activation or apoptosis involved in physiological processes such as coagulation and inflammation, including airway inflammation. We investigated the hypothesis that particulate matter causes the shedding of microparticles by human mononuclear and endothelial cells. Cells, isolated from the blood and the umbilical cords of normal donors, were cultured in the presence of particulate from a standard reference. Microparticles were assessed in the supernatant as phosphatidylserine concentration. Microparticle-associated tissue factor was assessed by an one-stage clotting assay. Nanosight technology was used to evaluate microparticle size distribution. Particulate matter induces a dose- and time- dependent, rapid (1 h) increase in microparticle generation in both cells. These microparticles express functional tissue factor. Particulate matter increases intracellular calcium concentration and phospholipase C inhibition reduces microparticle generation. Nanosight analysis confirmed that upon exposure to particulate matter both cells express particles with a size range consistent with the definition of microparticles (50–1000 nm). Exposure of mononuclear and endothelial cells to particulate matter upregulates the generation of microparticles at least partially mediated by calcium mobilization. This observation might provide a further link between airborne pollution and cardiopulmonary morbidity. Highlights: Exposure of cells to particulate causes shedding of prothrombotic microparticles The phenomenon is mediated by calcium mobilization. Microparticles could link exposure to particulate to cardiopulmonary morbidity.